Dynamic sedimentation measurements of physiological fluids in biomedical devices - Garcia, Valdemar (2012)
In this experimental work we investigate the flow of two different physiological fluids frequently used in microfluidic devices: physiological saline (PS) and dextran 40 (Dx40) containing about 6% of sheep red blood cells (RBCs), respectively. The capillaries were placed horizontally on a slide glass and the flow rate of the working fluids was kept constant. Images were obtained and analysed. Generally, the results show that PS and Dx40 have different flow behaviour due to the sedimentation of the RBCs.